PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN SIAK - Nur Fitri Fadila; Dedi Afandi; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTIndonesian physicians, in their daily practices, are set to hold firm to Indonesian Medical Codes of Ethics or Kode Etik Kedokteran Indonesia (KODEKI) as it composes moral values and norms in order to preserve professional nobleness in every situation that may persist. The ongoing National Health Insurance (NHI) that has been implemented since January 2014 has arose several challenges for physicians. The aim of this study was to discover the implementation of KODEKI value in NHC era in Siak Regency among general practitioners. This is a qualitative research using exploration method. Data was collected by interview technique and recorded by audio recorder. The results showed that all of the selected general practitioners possess altruism, responsibility, professional idealism, scientific and social integrity which are the values of KODEKI being observed in this research.Keywords: KODEKI, NHI, Siak Regency.